2006
DOI: 10.1097/01.blo.0000201152.98830.ed
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Osteochondral Allografts for Patellofemoral Arthritis

Abstract: Therapeutic study, Level IV (case series). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 44 publications
1
82
0
2
Order By: Relevance
“…Interestingly, however, for bipolar procedures, PF transplants have a better survival (though inferior to monopolar) than those in the tibiofemoral compartments. [27][28][29][30] Reported outcomes for PF osteochondral allograft are in the Table. Some other authors reported PF transplants as part of general case series of knee osteochondral allograft, but specific outcomes were not described. [33][34][35] Conclusions Fresh osteochondral allograft resurfacing of the PF joint is a challenging procedure owing to the complex anatomy of the central trochlea and patella.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, for bipolar procedures, PF transplants have a better survival (though inferior to monopolar) than those in the tibiofemoral compartments. [27][28][29][30] Reported outcomes for PF osteochondral allograft are in the Table. Some other authors reported PF transplants as part of general case series of knee osteochondral allograft, but specific outcomes were not described. [33][34][35] Conclusions Fresh osteochondral allograft resurfacing of the PF joint is a challenging procedure owing to the complex anatomy of the central trochlea and patella.…”
Section: Discussionmentioning
confidence: 99%
“…10,32 In another retrospective review of 14 fresh patellofemoral and patellar allografts, greater than half have been shown to survive over 10 years with significant improvement in knee scores and halted progression of patellofemoral osteoarthritis on radiographs. 33 Therefore, osteochondral allograft transplant of the PFJ is viewed as a salvage procedure for young, active patients who have failed other procedures and may not be candidates for the long rehabilitation protocol associated with ACI.…”
Section: Fresh Osteochondral Allograft Transplant Surgerymentioning
confidence: 99%
“…In this series, at the last follow-up, eight grafts were in place, four for more than 10 years and two for more than 5 years. Of the non-surviving allografts, three survived more than 10 years [37]. Jamali et al reported five failures in 20 knees (18 patients) treated for patellofemoral lesions [38].…”
Section: Clinical Evidencementioning
confidence: 99%